Komediowa „Eneida” - Piętka, Radosław (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2019)
Piętka Radosław, Komediowa „Eneida” (Comedy in Vergil’s Aeneid). The paper deals with the references – hypothetical and/or unquestionable – to comedy and comic conventions in the Aeneid of Vergil. Taking into consideration as many comic constituents as it is possible to retrieve from the Virgilian epic text, I would also like to try to answer the general question concerning supposed influence of these very constituents on the meaning of the whole text of the Aeneid.